Context and mechanisms of interprofessional learning during a Longitudinal Integrated Clerkship. Issue 3 (4th May 2022) - Gupta, Shalini; Howden, Stella
ABSTRACT: Longitudinal Integrated Clerkships (LIC) are known to afford several educational advantages to healthcare students including superior team working skills. This paper explores the perceptions of undergraduate medical students who undertook a rural LIC in Scottish primary care setting, to develop an understanding of their interprofessional learning (IPL) during the LIC placement. A qualitative approach was used to explore the lived experience of five LIC alumni who participated in this longitudinal study. They shared their experiences through written and audio diaries over a period of 1–2 months followed by individual semi-structured interviews. Transcripts were thematically analyzed to identify key themes related to IPL during LIC placements. Data from 12 audio and 9 written diaries and 5 interviews generated the following inter-woven themes with regards to various contextual factors, and the prominent generative mechanisms underlying the positive IPL experience: general practice setting afforded interprofessional interactions, longitudinality afforded interprofessional relationships, engagement in nurturing clinical teams, absence of hierarchy, flexibility and autonomy during the LIC, and 'goodwill' expressed toward the LIC programme. The significant interplay of enabling contextual factors and the generative mechanisms operating in the primary care practice environment is presented in context of existing research and proposed future developments.